3+9n-2=2n+4-3n

Simple and best practice solution for 3+9n-2=2n+4-3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+9n-2=2n+4-3n equation:


Simplifying
3 + 9n + -2 = 2n + 4 + -3n

Reorder the terms:
3 + -2 + 9n = 2n + 4 + -3n

Combine like terms: 3 + -2 = 1
1 + 9n = 2n + 4 + -3n

Reorder the terms:
1 + 9n = 4 + 2n + -3n

Combine like terms: 2n + -3n = -1n
1 + 9n = 4 + -1n

Solving
1 + 9n = 4 + -1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'n' to each side of the equation.
1 + 9n + n = 4 + -1n + n

Combine like terms: 9n + n = 10n
1 + 10n = 4 + -1n + n

Combine like terms: -1n + n = 0
1 + 10n = 4 + 0
1 + 10n = 4

Add '-1' to each side of the equation.
1 + -1 + 10n = 4 + -1

Combine like terms: 1 + -1 = 0
0 + 10n = 4 + -1
10n = 4 + -1

Combine like terms: 4 + -1 = 3
10n = 3

Divide each side by '10'.
n = 0.3

Simplifying
n = 0.3

See similar equations:

| (125x-108)/(14x-15)=8 | | K=2/3tc | | 2/3x-4/3 | | (125x-108)/(14x-15)8 | | 6x-4+8x=-4 | | (125*x-108)/(14*x-15) | | .25/.5=m/8 | | (4+i)-(2+3i)=0 | | 5x^2*6x^2= | | x-38=18-6x | | x+60*0+1=1 | | 9x+4(x+9)= | | 2/3•t=9 | | x+60*0+1=11 | | -2b-6+b-2= | | 2xy*x= | | x+60*0+1=61 | | 60+60*0+x=61 | | X=(2-3k)y | | 17/50=x/25 | | 0.04(y-6)+0.10y=0.12y-0.01(20) | | 9-17r=6 | | 60+x*0+1=61 | | 16o?8=56 | | (1+r)-(1+g)=9 | | 6(x-1)=3(x-5) | | 2100/6 | | 28-2x=18 | | F(2)+1=3(2)+1+2 | | D/5=-22 | | W/4=1.2 | | 3a-39ab= |

Equations solver categories